Sequestration of Potential Enzymes from Mushrooms compost waste. Issue 1 (April 2021) - Surendran, G; Karunakaran, S; Prabhu, N; Karthika Devi, S; Gajendran, T
Abstract: Mushrooms are type of white-rot fungi such as basidiomycetes, which degrades a lot of agro wastes by the secretion of precious bioconversion enzymes and produce the final enriched product. These enzymes take part in organic and inorganic waste remediation in the environment. This review analysed from the standpoint of scientists reserching in lignolytic enzyme production from various mushroom cultivation and also highlights the role of recent approaches within the production of giant volume of commercially important enzymes from biodegradable wastes. Then the proceeding work is to survey the novel lignolytic enzyme production aspects and their major characteristics, microbial sources such as basidiomycetes (white-rot fungi), downstream processing, relevant biochemical properties, diverse applications, enzyme mycotechnology and some recent research developments.